Reporting of paediatric exercise-induced respiratory symptoms by physicians and parents: an observational prospective study (Swiss Medical Weekly, 2025)
STUDY AIMS: Routinely collected health data are increasingly used for research; however important anamnestic details may be missing from medical records. We compared physician documentation of paediatric exercise-induced respiratory symptoms in clinical notes with parental questionnaire responses for the same children.METHODS: We analysed data from the Swiss Paediatric Airway Cohort (SPAC), a multicentre observational study of children treated in Swiss outpatient pulmonology clinics. We included children aged 6 to 17 years who were referred to a paediatric pulmonologist for evaluation of exercise-induced respiratory symptoms. Features of exercise-induced respiratory symptoms recorded by physicians were extracted from outpatient clinic letters transmitted to the referring physician, while parent-reported exercise-induced respiratory symptom data was collected from a standardised questionnaire completed at Swiss Paediatric Airway Cohort enrolment. We calculated agreement between physician-documented and parent-reported exercise-induced respiratory symptom characteristics using Cohen’s and Fleiss’s kappa.RESULTS:Of 1669 children participating in the Swiss Paediatric Airway Cohort (2017–2019), 193 (12%) met the inclusion criteria, of whom 48% were girls. Physicians provided detailed information on exercise-induced respiratory symptoms in 186 (96%) outpatient clinic letters. Documented characteristics included: type of physical activity triggering exercise-induced respiratory symptoms (69%), location of exercise-induced respiratory symptoms in chest or throat (48%), respiratory phase of exercise-induced respiratory symptoms (45%) and timing of exercise-induced respiratory symptoms during or after exercise (37%). Previous bronchodilator use (94%) and its effect on exercise-induced respiratory symptoms (88%) were consistently documented by physicians. The clinic letters for children diagnosed with dysfunctional breathing more often contained detailed exercise-induced respiratory symptom characteristics than those diagnosed with asthma. The level of agreement between physician-documented and parent-reported exercise-induced respiratory symptoms was moderate for use of bronchodilators (κ = 0.53) and poor-to-fair for all other features (κ = 0.01–0.36).CONCLUSION: This study highlights that outpatient clinic letters may lack some details on exercise-induced respiratory symptom characteristics – information that parents could provide. A standardised and detailed method for documenting paediatric respiratory symptoms in the coordinated data infrastructure may enhance future analyses of routinely collected health data.